Longitudinal tunnel ventilation control. Part 1: Modelling and dynamic feedforward control. (June 2017) - Euler-Rolle, Nikolaus; Fuhrmann, Martin; Reinwald, Markus; Jakubek, Stefan
Abstract: Road tunnels exceeding a certain minimum length are equipped with a ventilation system. In case of a fire it is used to achieve a predefined air flow velocity in the tunnel by adequately controlling the installed jet fans in order to ensure sufficient visibility for persons to safely follow the escape routes. As the dynamics of the air flow in road tunnels strongly depend on the tunnel length, short tunnels with longitudinal ventilation systems pose a challenging control task. In this paper, non-linear dynamic feedforward control is proposed for longitudinal ventilation control in case of an emergency. For this purpose, an analytical non-linear zero-dimensional model of the air flow is feedback linearised. Due to its special properties, which are presented and analysed, two different versions of feedforward control are proposed: One is focused on performance, the other on robustness. Finally, the beneficial behaviour of the presented two-degrees-of-freedom control approach is demonstrated by its application to an Austrian motorway tunnel. Abstract : Highlights: A zero-dimensional air flow velocity model for road tunnel ventilation is presented. Dynamic feedforward control of jet fans is found by feedforward linearisation. The resulting bifurcation characteristic is demonstrated and analysed. A robust scheme to feedforward control the ventilation system is developed. Results of the successful application to a road tunnel are shown.